Equilibrium and the Adjustment Process in the Number and Scope of Co-operatives in Morocco - Outla , Adil; Hamzaoui, Moustapha (Organizations and Markets in Emerging Economies, 2020)
The paper discusses the government policy that encourages the emergence of co-operatives and analyzes the co-operatives in light of their growth in number. It establishes a static equilibrium and highlights the co-operatives’ adjustment process (dynamic equilibrium). The methodology/approach consists of the development of a theoretical model, using the Nash equilibrium for the co-operative market, and the determination of a static equilibrium. It presents the data which includes variable measurements for the adjustment process for agricultural, artisanal, and fishery co-operatives in order to analyze the stochastic process of entry-and-exit flow of co-operatives. Accordingly, the paper estimates the co-operatives’ growth index speed of adjustment (SOA) as a function of the mean-reversion Ornstein–Uhlenbeck (OU) process. The theoretical results indicate that co-operatives’ earnings depend on the number of co-operatives, market-demand, and the capacity constraint. They also show that the margin for new entrants is a dynamic gap that especially depends on demand, capacity constraint and the profits. The empirical results indicate that co-operatives growth-index process is significantly mean reverting for all sectors, and the speed of adjustment for artisanal co-operatives is significantly higher than for those in agriculture and the fisheries.